2008
DOI: 10.1097/tp.0b013e3181705ad4
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte Globulin (ATG) Induction Therapy and Disease Recurrence in Renal Transplant Recipients With Primary IgA Nephropathy

Abstract: Recurrence of primary IgA nephropathy after renal transplantation is clearly a time-dependent event, justifying the use of Kaplan-Meier and Cox regression analyses to sort the significant risk factors. In this retrospective study, we focused on the potential role of induction immunosuppressive therapy. We studied 116 renal transplantation (84 males, 112 cadaveric donors, 95 first grafts, mean age at Tx=46.1 years) who received, as induction, antithymocyte globulin (ATG) in 29, anti-CD25 in 35, and none in 52, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
6
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 11 publications
4
61
6
2
Order By: Relevance
“…Indeed, there was no difference between azathioprine and mycophenolate mofetil or between cyclosporine and tacrolimus in the risk of graft failure caused by recurrence (18). In contrast, Berthoux et al (19) reported a protective role of anti-thymocyte globulins induction therapy in IgAN recurrence. In our population, we did not observe a statistically significant difference in immunosuppressive treatment between patients who relapsed and patients who did not (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, there was no difference between azathioprine and mycophenolate mofetil or between cyclosporine and tacrolimus in the risk of graft failure caused by recurrence (18). In contrast, Berthoux et al (19) reported a protective role of anti-thymocyte globulins induction therapy in IgAN recurrence. In our population, we did not observe a statistically significant difference in immunosuppressive treatment between patients who relapsed and patients who did not (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…There is now general agreement that the type and intensity of posttransplant immunosuppression does not influence the risk of IgAN recurrence. However, Berthoux et al (29) recently reported that the 10-year cumulative recurrence rate of IgAN was 9% (3 of 29) in patients who received induction with anti-thymocyte globulins versus 41% (21 of 52) in patients who did not receive such induction therapy. The authors hypothesized that the protective effect of anti-thymocyte globulins could be related to an augmented production of regulatory T cells.…”
Section: Iganmentioning
confidence: 99%
“…The factors associated to recurrence are not well understood: living donors, better HLA matching, short duration of the original disease, etc. There is yet no specific treatment for the recurrent disease; however in a retrospective study [56] we demonstrated that induction treatment with ATG seems able to reduce the incidence of recurrence in comparison to no induction or to induction with Basiliximab. A prospective randomized controlled trial comparing rabbit ATG to Basiliximab has already started, the PIRAT study: Prevention in IgA nephropathy recipients of full Recurrence After renal Transplantation according to induction immunosuppressive therapy: ATG versus Basiliximab.…”
Section: Renal Transplantation In Patients With Biopsy-proven Igan Onmentioning
confidence: 78%
“…First, a silent IgA nephropathy can be present on grafted kidney from apparently normal donors leading to the discovery of mesangial IgA deposits on graft biopsies performed early after transplantation; it was demonstrated in few cases that these deposits can regress and disappear demonstrating a contrario that the disease has a systemic (blood) transmission. Second, the original disease may reappear (recurrence) on the normal grafted kidney after few years and despite immunosuppression [51][52][53][54][55][56][57][58][59]. The cumulative incidence of clinicpathological recurrence is high reaching 35 % or more at 10 years post-transplant [56] and may lead to graft losses in up to 17 % at 10 y [57].…”
Section: Renal Transplantation In Patients With Biopsy-proven Igan Onmentioning
confidence: 99%
See 1 more Smart Citation